Sustainability and resilience of steel – shape memory alloy reinforced concrete bridge under compound earthquakes and functional deterioration within entire life-cycle. (15th November 2022) - Qian, Jing; Zheng, Yue; Dong, You; Wu, Honglei; Guo, Hongyuan; Zhang, Jiaxin
Highlights: A probabilistic framework of life-cycle sustainability and resilience is proposed. Earthquakes and deterioration processes are incorporated into the framework. The life-cycle cost-benefit analysis of the SMA-steel bridge is performed. The benefit of sustainability and resilience is observed for the SMA bridge. The new life-cycle insights contribute to carbon neutrality and a resilient city. Abstract: Bridges may suffer damage and failure from sudden earthquakes and continuous functional deterioration within their lifetime, resulting in severe consequences to both economy and society. The shape memory alloy (SMA) is a promising material with self-centering and corrosion-resistant characteristics. This study considers the steel-SMA reinforced concrete bridge as a potential alternative to mitigate the consequences induced by earthquakes and functional deterioration within its service life. Achieving carbon neutrality is an urgent goal due to the issues related to global warming, so herein the sustainability is necessarily assessed in terms of environmental, social, and economic metrics. Besides, structures are expected to recover their functionality after hazards efficiently. Thus, resilience describing the recovery ability of the structures needs to be assessed. A novel framework of life-cycle sustainability and resilience assessment is proposed and applied to assess the steel-SMA reinforced concrete bridge considering the stochastic process of earthquakes and functional deterioration, and the results are compared with those of the conventional bridge. The comparison results confirm that the steel-SMA reinforced concrete bridge is more sustainable and resilient under earthquakes and functional deterioration in a long-term perspective under the investigated scenarios. Specifically, it can contribute the carbon neutrality by reducing the long-term carbon dioxide emissions from transportation infrastructures.